2019
DOI: 10.1002/admt.201900564
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Polyaniline Nanofiber Networks toward High‐Performance Flexible Supercapacitors

Abstract: competitive for flexible devices. [10][11][12] Conductive polymers-based electrodes present good mechanical properties owning to the intrinsic flexibility of polymer chains, but show inferior energy capacity because of the bulk structure with limited surface area for ion storage and electrical conductivity for charge transfer. [13][14][15] Considering intrinsic flexibility and cost effectivity of conducting polymers, optimizing their structures and performances shows potential for practical applications. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…The required mechanical stability and flexibility of the device could be facilitated by the PVA. [201,202] Stress-strain studies revealed that the tensile modulus of MMT/PVA was higher (14.3 MPa with 22.6% breakage elongation) than pure PVA (9.58 MPa with 13.8% breakage elongation), and the enhanced mechanical features was ascribed to the plasticization effect of MMT. [203] TGA results suggested that MMT/PVA was thermally stable in the range of 50-300 °C, indicating the strong the hydrogen bonding interactions between MMT and PVA.…”
Section: Hydrogelsmentioning
confidence: 99%
“…The required mechanical stability and flexibility of the device could be facilitated by the PVA. [201,202] Stress-strain studies revealed that the tensile modulus of MMT/PVA was higher (14.3 MPa with 22.6% breakage elongation) than pure PVA (9.58 MPa with 13.8% breakage elongation), and the enhanced mechanical features was ascribed to the plasticization effect of MMT. [203] TGA results suggested that MMT/PVA was thermally stable in the range of 50-300 °C, indicating the strong the hydrogen bonding interactions between MMT and PVA.…”
Section: Hydrogelsmentioning
confidence: 99%
“…At the interface between the electrode and the electrolyte, the electrode stores and frees charges based on physical interactions or redox reactions [ 4 ]. Recent investigations have demonstrated that fSCs can be successfully integrated into complicated geometries with limited space, such as textiles and microscale devices, while preserving a high power density and a long cycle life [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Electrode materials used for fSCs typically include carbonaceous materials [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], metal oxides [ 13 , 14 , 15 , 16 , 17 ], and conductive polymers [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have demonstrated that fSCs can be successfully integrated into complicated geometries with limited space, such as textiles and microscale devices, while preserving a high power density and a long cycle life [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Electrode materials used for fSCs typically include carbonaceous materials [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], metal oxides [ 13 , 14 , 15 , 16 , 17 ], and conductive polymers [ 18 , 19 , 20 , 21 ]. Of all these, carbonaceous materials show promise as they generally demonstrate a remarkably high power density and a long cycle life.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Though, several kinds of renewable energy sources have attracted great attention including, rechargeable batteries, supercapacitors (SCs), and fuel cells. [1][2][3][4][5][6][7][8][9][10] Though, several kinds of renewable energy sources have attracted great attention including, rechargeable batteries, supercapacitors (SCs), and fuel cells.…”
mentioning
confidence: 99%
“…
laptops, rollup displays, and wearable devices. [1][2][3][4][5][6][7][8][9][10] Though, several kinds of renewable energy sources have attracted great attention including, rechargeable batteries, supercapacitors (SCs), and fuel cells. Among them, SCs hold great promise for fast charging, [11] while batteries take hours to recharge.
…”
mentioning
confidence: 99%